Palabra y lenguajes comunicativos en el ecuavoley - Alarcón Travéz, Rodrigo Israel (2014)
In the investigation it will talk each other on the communication and the sport, taking like study field to the sport of the ecuavoley, a definition of the same one happens, into what it has turned and transformed this one at present. There was tackled the topic of the sport as culture of identity and as it has been used like a practice of reproduction and social change along its existence. As in any sport, the ecuavoley possesses a regulation, sanctions, each of her respected by the sportsmen. Every player possesses strategies that are put into practice in the game, they possess nicknames that are for those who are known and with this one its physicist is demonstrated. The players of the ecuavoley, possess a bet that is the award of the winner. In the game of the ecuavoley the gestures, phrases or new words, they are created by the need to communicate in a new way, like that there was studied the meaning of all this new language, where kinésica and prosémica they intervene in this game.